Implikasi Tinjauan Dalam Mengeksplorasi Hubungan Antara Moralitas Dan Kejahatan - Audia Nervalina Purba; Taun Taun (Hakim, 2024)
Morality and evil are a very intertwined relationship where the consequences of the lack of application of morality will greatly affect the behavior of society which can lead to crime. Crime itself occurs because of a violation of morality or social deviation, which can harm an individual or society. Then the role of law which is the benchmark for a crime certainly has a very large contribution, where the integrity of law enforcement will greatly affect the continuity of morality in people's lives. Legal implications will have an impact in overcoming bad morality in society, and with this achievement, crimes that occur in people's lives will be minimal, if our awareness of the application of morality remains integrity.